Financial Reporting, Auditing, Analyst Scrutiny, and Investment Efficiency - Chan, Derek K. W.; Liu, Nanqin (The Accounting Review, 2022)
ABSTRACT This paper presents an economic framework to study strategic interactions along the analyst-auditor-owner disciplinary chain, in which the auditor examines the financial reports prepared by the owner, and the analyst uncovers financial misreporting, as well as audit failure. We find that although analyst scrutiny ex post detects misreporting, it ex ante aggravates the owner's misreporting behavior and further impairs financial statement reliability if the legal penalties for the auditor and the owner are small. We also show how the effects of a regulation depend on its target's disciplinarian(s). Specifically, (1) although enhancing the auditor's legal liability always increases audit quality and financial statement reliability, it decreases investment efficiency if and only if the analyst is highly independent, and (2) increasing the owner's misreporting penalty decreases investment efficiency if and only if either of (but not both) the regulations on the auditor and the analyst are strict. JEL Classifications: M41; M42; M48.